The Old Nubian Language - Smagina, Eugenia (punctum books, 2017)
Eugenia Smagina (Евгeния Б. Смaгина) first published her grammar of the Old Nubian language in 1986 in Russian. For more than thirty years the work has remained untranslated, even though the late Gerald M. Browne affirmed that "this lucid, well-argued presentation should be available to all Nubiologists and ought therefore be translated into a western language." Slavicist José Andrés Alonso de la Fuente has prepared a first English translation of this concise but indispensable work, which forms a necessary counterpart to Browne's classic Old Nubian Grammar. The grammar is divided into sections on script, lexicon, morphology, and syntax, and is followed by the analysis of a sample text, known as The Miracle of St. Mēnas. Smagina's The Old Nubian Language provides an excellent first introduction into the grammar of this medieval Nilo-Saharan language.